Natural rubber contributions to adaptation to climate change - Jacob, J.; Gitz, V.; Gohet, E.; Kadir, A.B.S.A.; Nair, L.; Pinizzotto, S.; Nguyen, A.N.; Blagodatsky, S.; Brady, M.A.; Cerutti, P.O.; Chen, B.; Duchelle, Amy E.; et al. (2022)
The purpose of this paper is to present research results relative to impacts of Climate Change on natural rubber production, potential means of adaptation and contribution of rubber to livelihoods resilience to climate change following a recent workshop organized by IRSG in collaboration with CIFOR/FTA, IRRDB and CIRAD. Climate change already impacts rubber production. In some regions longer dry seasons and more variable precipitations threaten the survival of young plants. Rubber has never been planted in areas with an average temperature higher than 28°C; as latex flow after tapping depends on temperature, higher temperatures may have a severe impact on production. Abnormal rains can also disrupt tapping. These modifications will drive a shift of climatically favourable areas. Most pests and diseases affecting rubber are strongly influenced by climate conditions.